The Philippine sectoral innovation system in textiles performance and challenges - Uldo, Angelito T.; Posadas, Roger D. (Quezon City University of the Philippines Diliman, 2014)
The study points out the industry's underperformance in terms of R&D activities, creation of new products, and skills development of employees and draws a pessimistic picture of the future of the sector. The main objectives of this report is to provide policy-makers and stakeholders in the textile industry with a comprehensive and holistic understanding of the sectoral innovation system, with focus on innovation performance and challenges. This paper also aims to be an instrument to help policy-makers identify key policy issues and set policy goals, specifically in creating innovation activities. The textile industry in the Philippines is a vital part of the country's economy. Textile manufacturing is of equal importance to the garment sector because it produces the necessary raw materials for the latter. The industry has experienced a rapid expansion during the 1960s and 1970s but has recently been on a decline due mainly to tougher conditions in export markets and failure to invest in new manufacturing technology. Various textile products embody the richness of the Philippine culture. Well-known traditional textile products showcase various weaving designs of the inabel of Ilocos, tiniri of Abra, hinabol of Bukidnon, t'nalak of South Cotabato, hablon of Iloilo, and inaul of Maguindanao. To this date, handloom weaving and dyeing using natural dyes still persist. However, according to Enriquez (2012) the younger generation had shifted into other economic activities and there's scarcity of the development of textile technologist. Thus, despite the competence in handloom weaving and finishing of textiles, it has been difficult to sustain the industry and to succeed in the mass production of these types of textiles technologist. Thus, despite the competence in handloom weaving and finishing of textiles, it has been difficult to sustain the industry and to succeed in the mass production of these types of textiles. The textile industry is vulnerable to political, technological and economic forces. War and political instability have interrupted several initial attempts to establish textile factories in the Philippines. Cottage-type textile production was popular in the country until 1940. In 1949, import controls were implemented to regulate the dollar outflow. It was only in the 1950s that the textile production was industrialized as motivated by the import-substitution scheme. When political instability rose in the 1980s, the decline of the textile manufacturing aggravated and the industry hardly regained its position. Apparently, competitors have superseded the Philippines because of technological advancement and development of technical human resource. In addition to this, the dynamics in the global market has largely affected the trade of textiles. The World Trade Organization imposed free trade and the ASEAN aimed to establish a regional trading block by 2015. More pressure was put on the Philippine textile industry to keep up with the competition. Over the years, it was observed that Philippine textile firms failed to develop their competitive advantage. PTRI has been pushing for the use of tropical fabrics as the source of this competitive advantage, but has not succeeded yet as of this writing. It was hoped that the tropical fabrics would provide the much needed differentiation of Philippine textiles from its rivals. In 2004, a law was even passed to use tropical fabrics in government uniforms, but it has not been widely implemented due to the limited number of capable textile firms to process such natural fibers.
The researcher used the analysis scheme framework developed by Bergek et al. (2005) to assess the Philippine Textile Innovation System. It has a description of a number of sub-analyses that needs to be taken by the researcher. The analysis scheme is composed of different steps such as the following : 1) Identifying the structural component of the Sectoral Innovation System (SIS), 2) Mapping the functional patterns of the SIS - this step consists of seven interlinked functional patterns proposed by Hekkert et al. (2007) which are entrepreneurial activities, knowledge development, knowledge diffusion through networks, guidance of the search, market formation, resources mobilization, and creation of legitimacy / counteract resistance to change, 3) assessing the functionality of the SIS and setting process goals, 4) identifying the mechanism inducing and blocking the functionality of the SIS, 5) identifying the key policy issues, and last 6) assessing the policy instruments and their likely effect on functional patterns.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Textile industry -- Philippines